Tamoxifen-independent recombination of reporter genes limits lineage tracing and mosaic analysis using CreERT2 lines - A. Álvarez-Aznar; I. Martínez-Corral; N. Daubel; C. Betsholtz; T. Mäkinen; K. Gaengel (Transgenic Research, 2020)
The CreER T2 /loxP system is widely used to induce conditional gene deletion in mice. One of the main advantages of the system is that Cre-mediated recombination can be controlled in time through Tamoxifen administration. This has allowed researchers to study the function of embryonic lethal genes at later developmental timepoints. In addition, CreER T2 mouse lines are commonly used in combination with reporter genes for lineage tracing and mosaic analysis. In order for these experiments to be reliable, it is crucial that the cell labeling approach only marks the desired cell population and their progeny, as unfaithful expression of reporter genes in other cell types or even unintended labeling of the correct cell population at an undesired time point could lead to wrong conclusions. Here we report that all CreER T2 mouse lines that we have studied exhibit a certain degree of Tamoxifen-independent, basal, Cre activity. Using Ai14 and Ai3, two commonly used fluorescent reporter genes, we show that those basal Cre activity levels are sufficient to label a significant amount of cells in a variety of tissues during embryogenesis, postnatal development and adulthood. This unintended labelling of cells imposes a serious problem for lineage tracing and mosaic analysis experiments. Importantly, however, we find that reporter constructs differ greatly in their susceptibility to basal CreER T2 activity. While Ai14 and Ai3 easily recombine under basal CreER T2 activity levels, mTmG and R26R-EYFP rarely become activated under these conditions and are therefore better suited for cell tracking experiments.